Electromagnetic field exposure as a plausible approach to enhance the proliferation and differentiation of mesenchymal stem cells in clinically relevant scenarios - Abdul Hamid, Haslinda; Sarmadi, Vahid Hosseinpour; Prasad, Vivek; Ramasamy, Rajesh; Miskon, Azizi (Zhejiang University Press, 2022)
Mesenchymal stem/stromal cell (MSC)-based therapy has been regarded as one of the most revolutionary breakthroughs in the history of modern medicine owing to its myriad of immunoregulatory and regenerative properties. With the rapid progress in the fields of osteo- and musculoskeletal therapies, the demand for MSC-based treatment modalities is becoming increasingly prominent. In this endeavor, researchers around the world have devised new and innovative techniques to support the proliferation of MSCs while minimizing the loss of hallmark features of stem cells. One such example is electromagnetic field (EMF) exposure, which is an alternative approach with promising potential. In this review, we present a critical discourse on the efficiency, practicability, and limitations of some of the relevant methods, with insurmountable evidence backing the implementation of EMF as a feasible strategy for the clinically relevant expansion of MSCs.